Give priority to abiotic factor of phosphate additives for pig manure composting to reduce heavy metal risk rather than bacterial contribution. (December 2021) - Wu, Juan; Chen, Wenjie; Zhao, Zichao; Zhang, Kui; Zhan, Yabin; Wu, Jing; Ding, Guochun; Wei, Yuquan; Li, Ji
Graphical abstract: Highlights: Labile phosphate additives had obviously diverse effects on the metals' species. K2 HPO4 benefit the stabilization of As, Mn and Zn and improve bacterial diversity. Cf and Er of heavy metals especially Cu and Mn in P, S and K were higher than CK. Key was pH not bacteria for metal speciation and risk under phosphate addition. Alkaline phosphate additives are suggested in practical applications. Abstract: Phosphate additives especially superphosphate can reduce nitrogen loss, and increase phosphorus availability in composting. This study investigated the changes of different heavy metals fractions and their relationship with bacterial community and abiotic factors during pig manure composting with adding equimolar H3 PO4, H2 SO4 and K2 HPO4 . Results showed that both acidic and alkaline labile phosphate increased the potential ecological risk of heavy metals compared to control, but K2 HPO4 decreased the accumulation of exchangeable Zn and Mn by 12% and 15% than that with H3 PO4 and H2 SO4 addition. Network analysis showed that K2 HPO4 enhanced the proportion of negative links in bacterial species with heavy metals, but H3 PO4 decreased the stability of bacterial network. Redundancy analysis demonstrated that pH was the key factor on metal speciation and risk with phosphate additives than bacterial role. The study presented theoretical basis for additive selection in controlling composting nitrogen fixation and environmental risk.